An Analysis of Building Statistics for the United States - Hubbard, Joseph B. (The Review of Economics and Statistics, 1924)
THE present survey was undertaken with two objects in view: (A) to analyze developments in the building industry in the light of current statistics and of the relationships shown between the construction industry and general business in the past and (B) to examine the data available for the volume of construction for the purpose of determining the statistical series suitable for current use. A summary of our conclusions follows. A